2015
DOI: 10.1007/978-3-319-15039-0_5
|View full text |Cite
|
Sign up to set email alerts
|

The High-Concentrator Photovoltaic Module

Abstract: High-concentrator photovoltaic (HCPV) modules incorporate solar cells, optical devices, cooling mechanisms, and other elements in an assembly to provide the functions required to concentrate sunlight and obtain electricity. The variety of designs for configuring HCPV modules is introduced in this chapter. Thermal management, an important aspect to be considered in the design of these modules, is discussed, as are the possibilities and innovations for implementing cooling mechanisms. The behavior of HCPV module… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(5 citation statements)
references
References 69 publications
0
5
0
Order By: Relevance
“…A soiling ratio of 0 occurs if soiling blocks all the sunlight from reaching the cell (100% soiling loss). Indexes similar to the soiling ratio, such as the Cleanness Index (Guo et al, 2015;Javed et al, 2017a), the Soiling Loss Factor (Tamizhmani et al, 2016), and the Soiling Factor (Rodrigo et al, 2020), can also be found in literature. All these indexes are based on the same concept as the r s : the ratio of the electrical output of a PV device to the output of the same device in clean conditions.…”
Section: Soiling Metricsmentioning
confidence: 99%
See 1 more Smart Citation
“…A soiling ratio of 0 occurs if soiling blocks all the sunlight from reaching the cell (100% soiling loss). Indexes similar to the soiling ratio, such as the Cleanness Index (Guo et al, 2015;Javed et al, 2017a), the Soiling Loss Factor (Tamizhmani et al, 2016), and the Soiling Factor (Rodrigo et al, 2020), can also be found in literature. All these indexes are based on the same concept as the r s : the ratio of the electrical output of a PV device to the output of the same device in clean conditions.…”
Section: Soiling Metricsmentioning
confidence: 99%
“…For these reasons, several models have already been presented to optimize the soiling mitigation strategy (i.e. maximize the difference between additional revenues and costs), depending on the environmental and economic characteristics of each site (Besson et al, 2017;Jones et al, 2016;Rodrigo et al, 2020;You et al, 2018). Despite their differences, all these models require an accurate monitoring of the losses and the understanding of their seasonality and inter-annual variability, which are discussed in this work.…”
Section: Introductionmentioning
confidence: 99%
“…The solar cell temperature depends upon many parameters, including ambient conditions called the concentrator standard test conditions (CSTCs), and not merely on its concentration and area of the cell. 42,43 The thermophysical properties of the different receiver layers are reported in Table 6.…”
Section: Heat Transfer Modelmentioning
confidence: 99%
“…Conduction is the primary mechanism for the transfer of the generated heat by the MJSC to the pin-fins heat sink, 44 which then is transferred to the ambient by both natural convection and radiation. 42 Increasing the concentration ratio results in increasing the short-circuit current (Isc) but at the same time reduces the open-circuit voltage (V oc ) due to the increase in the cell temperature. Different MJSCs coupled with CPV system exhibits an increase in the cell efficiency of up to 1000 suns, and then the cell efficiency drops due to the internal resistive losses.…”
Section: Assumptions and Boundary Conditionsmentioning
confidence: 99%
See 1 more Smart Citation